Ground‐level observation of a terrestrial gamma ray flash initiated by a triggered lightning. Issue 11 (14th June 2016) - Hare, B. M.; Uman, M. A.; Dwyer, J. R.; Jordan, D. M.; Biggerstaff, M. I.; Caicedo, J. A.; Carvalho, F. L.; Wilkes, R. A.; Kotovsky, D. A.; Gamerota, W. R.; Pilkey, J. T.; Ngin, T. K.; et al.
Abstract: We report on a terrestrial gamma ray flash (TGF) that occurred on 15 August 2014 coincident with an altitude‐triggered lightning at the International Center for Lightning Research and Testing (ICLRT) in North Central Florida. The TGF was observed by a ground‐level network of gamma ray, close electric field, distant magnetic field, Lightning Mapping Array (LMA), optical, and radar measurements. Simultaneous gamma ray and LMA data indicate that the upward positive leader of the triggered lightning flash induced relativistic runaway electron avalanches when the leader tip was at about 3.5 km altitude, resulting in the observed TGF. Channel luminosity and electric field data show that there was an initial continuous current (ICC) pulse in the lightning channel to ground during the time of the TGF. Modeling of the observed ICC pulse electric fields measured at close range (100–200 m) indicates that the ICC pulse current had both a slow and fast component (full widths at half maximum of 235 μs and 59 μs) and that the fast component was more or less coincident with the TGF, suggesting a physical association between the relativistic runaway electron avalanches and the ICC pulse observed at ground. Our ICC pulse model reproduces moderately well the measured close electric fields at the ICLRT as well as three independent magnetic field measurements made about 250 km away. Radar and LMA data suggest that there was negative charge near the region in which the TGF was initiated. Key Points: Best documented TGF observed at ground Second TGF induced by triggered lightning An ICC pulse occurred simultaneously (within 20 μs) of the TGF